Assessment Decision Support System Best Teacher By Using Analytical Hierarchy Process (AHP) Method - Hananto, April Lia; Priyatna, Bayu; Nurapriani, Fitria; Fauzi, Ahmad; Tukino, Tukino; Ahnaf, Naufal Zubdi (STMIK Dharma Wacana, 2022)
Assessment of teachers by the Principal of SMA Negeri 1 Kedungwaringin certainly needs to be done to determine the best teacher, so that teacher performance is in accordance with the specified competencies because the teacher is the most important and influential role in the world of education in the process of teaching and learning activities. The assessment was carried out not only for civil servants (PNS), including honorary teachers who also participated in the assessment process so that there were no limitations in evaluating teachers at SMA Negeri 1 Kedungwaringin. This assessment process uses the Analytical Hierarchy Process (AHP) Algorithm. The method used aims to determine the best teacher at SMA Negeri 1 Kedungwaringin who is in accordance with the assessment criteria prepared. The results of the ranking show that Dian Purwanti, S.Pd obtained the highest score of 0.342 out of 5 other teachers. This application is expected to assist school principals in determining the best teacher based on the criteria and weight of each existing value.